Rehabilitation after first-time anterior cruciate ligament injury and reconstruction in female football players: a study of resilience factors - Johnson, U.; Ivarsson, A.; Karlsson, J.; Hägglund, M.; Walden, M.; Börjesson, M. (BMC Sports Science, Medicine and Rehabilitation, 2016)
Background: Most of the research in the area of psychosocial factors in rehabilitation after sports injuries has focused on risk behaviors, while relatively few studies have focused on behaviors that facilitate rehabilitation. The objective of our study was to understand the psychosocial features that characterize elite female football players who express a resilient behaviour during rehabilitation after a first-time anterior cruciate ligament (ACL) injury and reconstruction. Methods: A qualitative method was used based on individual in-person interviews and video communication of players who incurred a first-time ACL tear during the 2012 season of the Swedish Women`s Elite Football League. In total, 13 players had a first-time ACL and were interviewed post-season. The interviews were followed by a thematic content analysis. Based on this, eight players were identified as showing resilient behaviors during their rehabilitation and were included in the final analysis. Results: Three core themes representing psychosocial factors that help players cope successfully with rehabilitation were identified: (I) constructive communication and rich interaction with significant others; (II) strong belief in the importance and efficacy of one`s own actions; and (III) the ability to set reasonable goals. Conclusions: The findings suggest three core themes of psychosocial factors that characterize first-time ACL-injured elite female football players showing resilience during rehabilitation after ACL reconstruction. Suggestions for medical teams about ways to support communication, self-efficacy, and goal-setting during the rehabilitation process, are provided.